The Impact Of Tele-Rehabilitation Nursing On The Daily Living Abilities Of Children With Cerebral Palsy - Zhao, Jing; Liu, Ying; Su, Junting; Sun, Guang; Xie, Huan (Pacific International Journal, 2024)
The objective of this study is to delve into the influence of tele-rehabilitation nursing on children diagnosed with cerebral palsy. To achieve this, we conducted a thorough search across multiple databases including the Cochrane Library, PubMed, ScienceDirect, CNKI, and WanFang Data, aiming to gather evidence on the efficacy of tele-rehabilitation for cerebral palsy. Subsequently, a comparative analysis was performed to assess the differences in physical structure, function, activities, and participation in daily living activities between children receiving tele-rehabilitation nursing and those undergoing home-based care. For the purpose of this investigation, a total of 30 subjects were divided into two groups: a control group that received tele-rehabilitation nursing, and an observation group that underwent traditional home-based rehabilitation. The findings of our data analysis revealed that tele-rehabilitation nursing significantly improved the daily living abilities of children with cerebral palsy, with statistical significance (P<0.05). Notably, children in the tele-rehabilitation group exhibited a significantly higher level of participation in daily activities compared to the home-based rehabilitation group, while no significant differences were observed in terms of physical structure, function, and activity levels.